Hashimoto's thyroiditis impairs embryo implantation by compromising endometrial morphology and receptivity markers in euthyroid mice - Zhangbi Wu; Yaojun Cai; Qin Xia; Tiantian Liu; Hao Yang; Fen Wang; Nan Wang; Zhen Yu; Chunying Yin; Qunan Wang; Defa Zhu (BMC, 2019)
Abstract Background Although thyroid dysfunction caused by Hashimoto's thyroiditis (HT) is believed to be related to implantation failure due to the underdevelopment of the receptive uterus, it is unknown whether HT itself, even in the euthyroid state, impairs embryo implantation associated with endometrial receptivity defects. To address whether HT itself can affect endometrial receptivity accompanied by implantation alterations, a euthyroid HT model was established in mice. Methods Female NOD mice were immunized twice with thyroglobulin and adjuvant to induce the experimental HT model. Four weeks after the second treatment, the mice were normally mated, and pregnant ones were sacrificed in implantation window for thyroid-related parameter and steroid hormones measurements by electrochemiluminescence immunoassay and enzyme-linked immunosorbent assay and implantation site number calculation by uptake of Chicago Blue dye. In addition, certain morphological features of endometrial receptivity were observed by hematoxylin-eosin staining and scanning electron microscopy, and the expression of other receptivity markers were analyzed by immunohistochemistry, RT-qPCR or Western Blot. Results HT mice displayed intrathyroidal monocyte infiltration and elevated serum thyroid autoantibody levels without thyroid dysfunction, defined as euthyroid HT in humans. Euthyroid HT resulted in implantation failure, fewer pinopodes, retarded pinopode maturation, and inhibited expression of receptivity markers: estrogen receptor α (ERα), integrin β3, leukemia inhibitory factor (LIF), and cell adhesion molecule-1 (ICAM-1). Interestingly, despite this compromised endometrial receptivity response, no statistical differences in serum estradiol or progesterone level between groups were found. Conclusions These findings are the first to indicate that HT induces a nonreceptive endometrial milieu in the euthyroid state, which may underlie the detrimental effects of HT itself on embryo implantation.